A dentate‐stamped Lapita dish from the central south coast of Papua. Issue 1 (27th January 2022) - Sand, Christophe; Miamba, Kenneth; Kuaso, Alois; Araho, Nick; Allen, Jim
Abstract: The chance recovery of a large pottery sherd from a flat‐bottomed dish with dentate‐stamped decoration in Galley Reach, about 50 km northwest of Port Moresby, raises interesting questions concerning interactions between Lapita arrivals and the established Melanesian communities of mainland Papua New Guinea. While the geographical proximity of the find to the Caution Bay Lapita sites would suggest some connection, an analysis of the sherd indicates that it may be older than Lapita at Caution Bay. Comparisons with Island Melanesian Lapita sites indicate that the sherd is mid‐ to late Lapita in age, both in its form and decoration. As such, it joins the corpus of chance PNG mainland and near mainland Lapita finds of similar age. This developing pattern may have a different genesis to the Lapita dispersal into Remote Oceania and instead reflect trade‐based connections between island and mainland communities in the first millennium BC. The data remain ambiguous on this point. Résumé: La découverte fortuite dans l'estuaire de Galley Reach à environ 50km au nord‐ouest de Port Moresby, d'un tesson de poterie de grande dimension provenant d'une assiette à fond plat et comportant un décor pointillé, soulève d'intéressantes questions sur les relations entre des groupes Lapita et les communautés mélanésiennes établies sur la grande île de Papouasie Nouvelle‐Guinée. Bien que la proximité géographique de cette découverte avec les sites Lapita de Caution Bay permette d'envisager un lien général, une analyse du tesson indique que celui‐ci est probablement plus ancien que les vestiges Lapita de Caution Bay. Les comparaisons avec des sites Lapita de Mélanésie insulaire montrent que le tesson est, dans sa forme autant que par son décor, de tradition Lapita classique à tardive. Il intègre ainsi le corpus des découvertes Lapita fortuites de même époque réalisées sur l'île continentale et les îles proches. Un modèle différent de celui à l'origine de la dispersion vers l'Océanie lointaine pourrait être associé à ces vestiges, reflétant plutôt des relations d'échanges entre des communautés insulaires et de la grande île au cours du premier millénaire avant J.C. Les données restent ambigües sur ce point.